The role of emergency departments in opioid related harms: A qualitative study among emergency healthcare providers - Charlotte Ten Pas; Viren Bahadoer; Cornelis Kramers; Albert Dahan; Hannah Ellerbroek; Joris Holkenborg; Ozcan Sir; Merel Van Loon; Arnt Schellekens; Nicole Kraaijvanger (PLoS ONE, 2025)
Objectives Opioids are commonly prescribed in the Emergency Department (ED) for acute pain management. However, their use carries significant risks, including dependence and misuse. This study aims to gain insight into the perspectives of ED physicians and physician assistants (PAs) concerning the multifaceted role of the ED in problematic opioid use. This is crucial for reducing opioid-related harms. Design A qualitative study, using semi-structured interviews. Setting and participants Interviews were conducted with twenty-five ED physicians and PAs from four hospitals in the Netherlands. A diverse group participated in the study, representing different hospital settings and levels of working experience, Outcome measures and analysis Reflexive thematic analysis was performed to develop key themes reflecting participants’ perspectives and attitudes towards the role of the ED in opioid related harms. Results Two key themes were developed from the analysis. The first theme ‘Preventing opioid-related harms from an ED perspective’ underscores the careful approach emergency physicians take when prescribing opioids. This involves restricting opioid prescriptions to specific indications, considering alternative pain management options, limiting prescription durations, and involving patients in shared decision-making. Beyond their own prescribing practices, emergency care providers also collaborate with general practitioners, navigate patient expectations, and operate within a broader societal landscape where pain is increasingly viewed as intolerable. The second theme ‘Managing problematic opioid use at the ED’ highlights the difficulties faced by emergency care providers in treating individuals who are already using or dependent on opioids. This includes recognizing, intervening, referring, and managing cases of problematic opioid use. This theme also considers the involvement of other healthcare professionals, such as pain specialists and psychiatrists, as well as the roles and responsibilities of patients. Additionally, it considers the broader societal context, particularly the extent of opioid-related harms in the Netherlands, Conclusions This study sheds light on the complexities surrounding opioid use and emergency care providers’ approach to mitigating opioid related harms while navigating patient needs and systemic challenges. EDs play a critical role in addressing opioid-related harms but face significant challenges. Strengthening provider education, integrating patient records, and enhancing partnerships with addiction services are key steps toward refining healthcare responses and policies for this ongoing public health crisis.